2015
DOI: 10.1016/j.engstruct.2015.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Fire performance of blind-bolted connections to concrete filled tubular columns in tension

Abstract: This paper describes an advanced numerical model to predict the fire behaviour of blind-bolts in the tension area of endplate connections between I-beams and concrete filled tubular (CFT) columns. It is the continuation of a previous research on the thermal response of connections, considering the tension load of a moment-resisting connection. Due to the absence of experiments and data on blind-bolts fire performance the aim was to provide a model for their study. The effect of two main variables was researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 30 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The increase of the FRR achieved using FR steel bolts was determined by comparison with normal HSS bolts. FR steel bolts properties were defined following the recommendations from Sakumoto et al [27], while HSS capacity was extracted from Eurocode 3 Part 1.2 Annex D [41] In a previous work from the authors, Pascual et al [9], it was observed that in connections to hollow steel columns in fire, at the failure instant, stresses exceeded the capacity of both, sleeve and shank. Nonetheless, in connections to CFST columns, the sleeve underwent less stresses and the shank was the compromising part for the connection.…”
Section: Fire Resistant Steel Boltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the FRR achieved using FR steel bolts was determined by comparison with normal HSS bolts. FR steel bolts properties were defined following the recommendations from Sakumoto et al [27], while HSS capacity was extracted from Eurocode 3 Part 1.2 Annex D [41] In a previous work from the authors, Pascual et al [9], it was observed that in connections to hollow steel columns in fire, at the failure instant, stresses exceeded the capacity of both, sleeve and shank. Nonetheless, in connections to CFST columns, the sleeve underwent less stresses and the shank was the compromising part for the connection.…”
Section: Fire Resistant Steel Boltsmentioning
confidence: 99%
“…The use of new bolt materials represents a method of enhancement at room and elevated temperatures [9][10]…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of blind-bolts, the Hollo-bolt system (Lindapter International, UK) was chosen due to its easy assembly and its feasibility to bear bending moments [10], in particular, a modified version that is anchored into the concrete to increase the connection stiffness [9]. At room temperature the blind-bolt performance has been addressed, but under fire conditions the knowledge is still scarce [7,8]. This research tries to increase the insight by considering an important aspect as it is the effect of the slim-floor.…”
Section: Thermal Behaviour In Blind-bolted Connections To Concrete-fimentioning
confidence: 99%
“…They confirmed that the pull-out resistance of the EHB is higher than the tensile capacity of the internal bolt of the EHB and that the behaviour of the EHB is comparable to standard bolt in terms of stiffness, strength and failure mechanism, which makes it suitable for use in moment-resisting connections. Other studies on the EHB included studying its fatigue behaviour (Tizani et al 2014) and its behaviour in fire (Pascual et al 2015).…”
Section: Introductionmentioning
confidence: 99%